Short-Term Ketogenic Diet Induces a Molecular Response That Is Distinct From Dietary Protein Restriction - Kalafut, Krystle C.; Mitchell, Sarah J.; MacArthur, Michael R.; Mitchell, James R. (Frontiers in Nutrition, 2022)
There is increasing interest in utilizing short-term dietary interventions in the contexts of cancer, surgical stress and metabolic disease. These short-term diets may be more feasible than extended interventions and may be designed to complement existing therapies. In particular, the high-fat, low-carbohydrate ketogenic diet (KD), traditionally used to treat epilepsy, has gained popularity as a potential strategy for weight loss and improved metabolic health. In mice, long-term KD improves insulin sensitivity and extends lifespan and healthspan. Dietary protein restriction (PR) causes increased energy expenditure, weight loss and improved glucose homeostasis. Since KD is inherently a low-protein diet (10% of calories from protein vs. 20% in control diet), here we evaluated the potential for mechanistic overlap between PR and KD via activation of a PR response. Mice were fed control, protein-free (PF), or one of four ketogenic diets with varying protein content for 8 days. PF and KD diets both decreased body weight, fat mass, and liver weights, and reduced fasting glucose and insulin levels, compared to mice fed the control diet. However, PF and KD differed with respect to insulin tolerance and hepatic insulin sensitivity, which were increased in PF-fed mice and impaired in KD-fed mice relative to controls. Furthermore, contrary to the PF-fed mice, mice fed ketogenic diets containing at least 5% protein did not increase hepatic Fgf21 or brown adipose Ucp1 expression. Interestingly, mice fed KD lacking protein demonstrated greater elevations in hepatic Fgf21 than mice fed a low-fat PF diet. To further elucidate potential mechanistic differences between PF and KD diets and the interplay between dietary protein and carbohydrate restriction, we conducted RNA-seq analysis on livers from mice fed each of the six diets and identified distinct gene sets which respond to dietary protein content, dietary fat content, and ketogenesis. We conclude that KD with 10% of energy from protein does not induce a protein restriction response, and that the overlapping metabolic benefits of KD and PF diets occur via distinct underlying mechanisms.